Achieving Ultra‐High Heat Flux Transfer in Graphene Films via Tunable Gas Escape Channels - Haolong Zheng; Peng He; Shujing Yang; Yonghua Lu; Na Guo; Yanhong Li; Gang Wang; Guqiao Ding (Advanced Science)
Abstract Graphene films have been applied in the thermal management of electronic devices due to their high thermal conductivity. However, the ever‐increasing power and local heat flux density of electronic chips require graphene films with excellent heat flux carrying capacity. Enhancing the heat flux carrying capacity is highly challenging, and the key is to maintain high thermal conductivity while increasing film thickness. Gases released during film assembly and the resulting catastrophic structural destruction should be responsible for the trade‐off between film thickness and thermal conductivity. Herein, the evolution of the pore structure is investigated during the assembly of graphene films and propose the construction of gas escape channels for the preparation of thick graphene films. The process involves using humidification treatment and freeze‐drying GO films to pre‐construct the ordered flat pore structure. The microstructure optimization of graphene films with more order, fewer wrinkles and defects, and larger grain size is achieved. After optimization, graphene films with ultra‐high thermal conductivity (1781 W m−1 K−1) and a thickness over 100 µm are realized. These films exhibit exceptional heat dissipation and cooling capabilities in high heat flux density (≈2000 W cm−2). This finding holds significant potential for guiding the thermal management of high‐power devices.